Rules of solving 3x3x3 Rubik's Cube Based on permutation of the group theory / Maizatul Asyirah Makhtar, Najihah Abdullah and Noor Hafizan Zul Apandi - Makhtar, Maizatul Asyirah (2018)
Pennutation is a part of group theory which is a one-to-one function and onto (bijective function) that maps on the finite number of sets. Since the movement of Rubik's Cube is a one-to-one function, it uses pennutation method to solve it from the shuffled state unti I it becomes identity. Rubik's Cube is not a puzzle that can be solved by sheer luck. Without knowing that there exist a simpler way in solving the Rubik's Cube, most people find it difficult and stressful. The objectives of this study is to generate the Rubik's Cube rules based on Fridrich and Layer-by-Layer method using groups of permutation in group theory. Besides that this study also aims to analyse the average total movements in solving Rubik's Cube using Maple software. The first phase of this research is suggesting two alternatives in solving Rubik's Cube for beginners which are based on Fridrich and Layer-by-Layer method. The final phase is to analyse the average total movements for both alternative I and 2. Concluded in this study, alternative 2 give the least movement required to solve the Rubik's Cube and help in reducing time consuming. This study will act as a fundamental programming to come out with an advanced system using mathematics software. It also provides an encouragement for the beginners to solve the Rubik's Cube in a higher level in terms of different sizes and shapes of Rubik's Cube